Pengaruh Sediaan Deodoran Krim Kombinasi Destilat Daun Sirih Hijau (Piper betle L.) dan Kulit Kayu Manis (Cinnamomum burmannii) Terhadap Pertumbuhan Staphylococcus aureus - Mulyani, Elma Tri; Suwandi, Edy; Sari, Emilda (Jurnal Laboratorium Khatulistiwa, 2025)
Cream deodorant is a topical preparation used to reduce body odor caused by Staphylococcus aureus bacteria in sweat glands. The purpose of this study was to determine the effect of a cream deodorant preparation containing a combination of green betel leaf and cinnamon bark at concentration of 10%, 20%, and 30%  on inhibiting the growth of Staphylococcus aureus bacteria. Synthetic deodorants containing alumunium chloralhydrate have the potential to cause negative side effects, including cancer risk. Essential oils from green betel leaf and cinnamon bark contain antibacterial compounds such as betephenol and cinnamaldehyde, which work synergistically as active ingredients. This study used a purposive sampling technique and the well diffusion method on MHA medium. 10 replications were conducted, resulting in 30 samples. The results showed that the inhibition zone at a concentration of 10% is on average 13,4 mm (strong), at a concentration of 20%, it is on average 20.5 mm (very strong) and at a concentration of 30%, it is on average 23,5 mm (very strong). The results of a simple linear regression statistical test showed a significance value (p=0.000 → p < 0.05), indicating a significant effect of concentration on inhibitory power. This study concludes that the cream deodorant preparation containing the combination of green betel leaf and cinnamon bark distillate was effective in inhibiting Staphylococcus aureus, with the highest inhibition zone at a concentration of 30%. This combination has the potential to be developed as a safe, natural antibacterial deodorant ingredient.